2014
DOI: 10.1111/evj.12331
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic respiratory endoscopic findings pre‐ and post laryngoplasty inThoroughbred racehorses

Abstract: Multiple forms of DUAO occurred pre-LP and additional forms often developed post LP. Post LP the degree of arytenoid cartilage abduction at rest was useful to predict the degree of abduction during exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 25 publications
4
61
3
1
Order By: Relevance
“…We, therefore, believe that the improved exercising grades obtained after surgery in our study were due to the reinnervation. Several other studies in which resting and exercising endoscopy post-laryngoplasty were compared revealed a loss of arytenoid abduction during exercise compared with the resting abduction in 21% [20], 37% [22] and 45% [23] of the horses investigated, which was not observed in our study. In exercising grade C, the left arytenoid is less abducted than in the natural resting position [14] and, logically, this restricts airway flow.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…We, therefore, believe that the improved exercising grades obtained after surgery in our study were due to the reinnervation. Several other studies in which resting and exercising endoscopy post-laryngoplasty were compared revealed a loss of arytenoid abduction during exercise compared with the resting abduction in 21% [20], 37% [22] and 45% [23] of the horses investigated, which was not observed in our study. In exercising grade C, the left arytenoid is less abducted than in the natural resting position [14] and, logically, this restricts airway flow.…”
Section: Discussioncontrasting
confidence: 78%
“…In recent papers describing exercising endoscopy post-laryngoplasty, DUAO was observed in 37-58% of cases [22,23]. After reinnervation surgery, horses may have low resting abduction grades because the C1/C2 nerve is only activated during forced respiration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous URT abnormalities showed weak‐to‐negligible agreement in disorder grade/appearance between putatively identical OGE examinations, with conditions such as PI, MDAF, epiglottic grade and iDDSP (at all exercise stages) variable in the direction of the change in grade/appearance. Previous publications have also demonstrated changes in URT abnormalities between OGE examinations, although surgical treatment conducted between examinations and/or undiagnosed pre‐existing or newly developed URT disease(s) were hypothesised to induce these changes . Duration of time between OGE examinations in this study did not significantly affect variability for the majority of URT disorders.…”
Section: Discussioncontrasting
confidence: 42%
“…Overground endoscopy (OGE) is now commonly used for diagnosis of upper respiratory tract (URT) disorders in horses during exercise . However, variability in exercising endoscopy findings have been recognised to occur in association with different exercise intensities, head positions, tack and inter‐observer variation in URT disorder grading .…”
Section: Introductionmentioning
confidence: 99%